Buried SiGe as a performance booster in n-channel FDSOI MOSFETs. (December 2019) - Clifton, Paul; Goebel, Andreas; Mulfinger, Robert; Child, Amy; Straub, Sherry; Sporer, Ryan; Carter, Rick; Kluth, Jon; Schaeffer, Jamie; Nguyen, Bich-Yen; Chabanne, Guillaume; Daval, Nicolas; et al.
Highlights: Straining of FDSOI demonstrated by elastic edge relaxation of a buried SiGe stressor. Ultra-thin body and ultra-thin BOX wafers fabricated with SiGe under the buried oxide. Strain imaging shows 0.5% tensile strain in the FDSOI and relaxation of the SiGe layer. n-channel MOSFETs fabricated in a foundry FDSOI process have 9% higher drive current. Abstract: We report for the first time the implementation of SiGe buried stressors in the context of research and development of an advanced foundry FDSOI process and the observation of improved transconductance and current drive performance of n-channel FDSOI MOSFETs. Epitaxial SiGe stressors grown by CVD at Applied Materials were incorporated under the buried oxide of 300 mm FDSOI wafers by Soitec using lower temperature SOI bonding, splitting and thinning processes and the wafers were subsequently processed through an FDSOI development line at GLOBALFOUNDRIES. The use of FDSOI with buried stressor under the BOX eliminates the risk of extended defects in the epitaxial SiGe layer penetrating up into the SOI channel and also provides an opportunity to obtain a high level of strain in any semiconductor on insulator. A 70 nm thick SiGe buried stressor with 20% Ge is shown to provide a 10% improvement in Idsat at a fixed Ioff for n-FETs with 20 nm gate length and transconductance, gm is correspondingly improved by 15%.